What Are Strategies For Increasing Sales In E-Commerce - Agus Mokodompit, Eliyanti; Maryoso, Slamet; Maulida, Sofia (Journal of Management, 2024)
Digitalization has a broad and significant impact on economic situations. E-Commerce is commonly defined as electronic buying and selling transactions via the internet. The purpose of this study is to identify important changes and types of behavioral change in Bandung customers who use e-commerce before and during the digitalization period. This is considered quantitative research. The study's population and sample size were 112 respondents. The collected data was analyzed using linear regression. The regression coefficient results indicate that the constant has a large impact on consumer behavior, with a high level of statistical significance. This demonstrates that, even at the zero sales level, the value is not statistically significant, despite having a significant consumer behavior level coefficient. However, there are coefficients for the independent variables. These findings suggest that, in the context of this study, increasing sales volume had no meaningful impact on consumer behavior. The study concluded that there was no substantial change in consumer behavior toward e-commerce in Bandung Regency.